Surgical Treatment of Obstetric Plexus Lesions by Direct Coaptation Compared to Sural Nerve Graft Interposition - Justus Mai; Christa Kunigunde Raak; Thomas Ostermann; Jörg Bahm; Wolfram Scharbrodt (Journal of Brachial Plexus and Peripheral Nerve Injury)
Background To date, there are no uniform guidelines for the treatment of obstetric plexus lesions in German-speaking countries. An end-to-end direct suture after resection of trunk neuroma is recommended for surgical treatment if tension-free coaptation is possible, whereas the use of autologous nerve grafts bridging the gap between the adaptation margins is advised by consensus if tension-free coaptation is impossible.